Quantum fluctuations on top of a PT-symmetric Bose-Einstein condensate - Xiaoling Cui (Physical Review Research, 2022)
We investigate the effects of quantum fluctuations in a parity-time (PT) symmetric two-species Bose-Einstein condensate (BEC). It is found that the PT symmetry, though preserved by the macroscopic condensate, can be spontaneously broken by its Bogoliubov quasiparticles under quantum fluctuations. The associated PT-breaking transitions in the Bogoliubov spectrum can be conveniently tuned by the interaction anisotropy in spin channels and the strength of PT potential. In the PT-unbroken regime, the real Bogoliubov modes are generally gapped, in contrast to the gapless phonon mode in Hermitian case. Moreover, the presence of PT potential is found to enhance the mean-field collapse and thereby intrigue the droplet formation after incorporating the repulsive force from quantum fluctuations. These remarkable interplay effects of PT symmetry and interaction can be directly probed in cold atoms experiments, which shed light on related quantum phenomena in general PT-symmetric systems.